Extraction of junctions, lines and regions of irregular line drawing : the chain code processing algorithm - Haron, Habibollah; Mohamed, Dzulkifli; Shamsuddin, Siti Mariyam (Penerbit UTM Press, 2003)
Conceptualization stage in designing engineering product is a process of translating engineer’s idea onto a sheet of paper. The product is always sketched on a sheet of paper using pencil. The sketch is tidied up by adding accurate dimension, and complete view of hidden part. This paper discusses part of the process involved in translating the sketch or irregular line drawing into a tidy or regular line drawing, that yield three important entities namely junction, line and region. The chain code algorithm is used to find these entities. The paper also explains explicit thinning process involved before the chain code methodology. Assumptions, important definitions and method of loading image file are also presented. The paper is concluded with several test input sketches, conclusion and future works.